Loneliness and frailty among nursing home older adults: the multiple mediating role of social support and resilience. Issue 6 (20th September 2021) - Zhao, Xia; Si, Huaxin
Abstract: Background: Loneliness has been considered as a risk factor for frailty. Social support (as an external protective resource) and resilience (as an inner protective resource) might play protective roles on the association between loneliness and frailty. In this study, the mediating roles of social support and resilience between loneliness and frailty were explored among older adults living in nursing homes. Methods: Older adults (N = 210) from three nursing homes in China were recruited in this cross‐sectional study. Information for sociodemographic variables, frailty, loneliness, social support and resilience were collected. The bootstrap analyses by PROCESS macro were conducted to test the multiple mediating role of social support and resilience between loneliness and frailty. Results: The prevalence of frailty was 34.8% among older adults in nursing homes. Also, social support and resilience mediated the association between loneliness and frailty, respectively. Furthermore, the multiple mediating testing results showed that social support and resilience played sequential mediating roles in the link of loneliness to frailty. Conclusions: The findings underscore the protective role of social support and resilience of loneliness and frailty among nursing home older adults.